Footprints in the Sands of Time: A Comparative Analysis of the Effectiveness of Customer Satisfaction and Customer–Company Identification over Time. (November 2014) - Haumann, Till; Quaiser, Benjamin; Wieseke, Jan; Rese, Mario
Previous research has identified customer satisfaction and customer–company identification as two of the most important concepts in relationship marketing. Yet despite their proclaimed importance, research on their long-term effectiveness is surprisingly scarce. Furthermore, comparative research acknowledging the concepts' different theoretical roots and illuminating the differences in their long-term effectiveness is lacking. In addition, little is known about how competitive actions affect the long-term effectiveness of both concepts. This study makes a first attempt to address these research gaps and offers a comparative analysis of the effectiveness of customer satisfaction and customer–company identification in driving important customer outcomes over time. Latent growth analyses of rich longitudinal data from customers over nine measurement points spanning 43 weeks (n = 6, 930) show that customer satisfaction and customer–company identification have positive initial effects on customers' loyalty and willingness to pay but differ in their ability to maintain these positive effects over time. Whereas the positive effects of customer satisfaction decrease more rapidly, the effects of customer–company identification are significantly more persistent. Analysis of the moderating effects of relative competitive advertising suggests that customer–company identification is more effective at immunizing customers against competitive actions.